An Analyisis Of Students’ Difficulties In Listening Comprehension At Class XI Mipa 2 Of Sma Swasta Pembda 1 Gunungsitoli In 2023/2024 Academic Year - Suci Wahyuni Marunduri; Suparjo Suparjo; Esraweddi Siregar; Sondang Manik; Lastri Wahyuni Manurung (Universitas Pahlawan Tuanku Tambusai, 2023)
One of the key skills in the educational process of learning English is listening comprehension skill. Despite its significance in English learning, most students find it difficult to master when practicing listening comprehension. This research aims to analyze the difficulties that students most frequently encounter with listening comprehension particularly at class XI MIPA 2 SMA Swasta Pembda 1 Gunungsitoli in 2023/2024 academic year. The research approach used in this research was descriptive qualitative. 36 students of class XI MIPA 2 were chosen as samples using the cluster sampling technique. Questionnaires were used to gather the data. All students in the class received the questionnaire from the researcher. The research findings demonstrated that the listening material, the listener, and the physical setting were all related to the difficulties the students faced in comprehending what they were listening